Pro Spring - Harrop, Rob. (Apress : Imprint: Apress, 2005)
Spring—the open source Java–based framework—allows you to build lighter, better performing applications. Written by Spring insiders Rob Harrop and Jan Machacek, Pro Spring is the only book endorsed by Rod Johnson, founder of the Spring Framework. At over 800 pages, this is by far the most comprehensive book available and thoroughly explores the power of Spring. You'll learn Spring basics and core topics, as well as share the authors' insights and real–world experience with remoting, mail integration, hibernate, and EJB. From the foreword: “Rob's enthusiasm for Spring—and technology in general—is infectious. He has a wide range of industry experience and a refreshingly practical, common sense approach to applying it. All those qualities come out in this book. It's evident on nearly every page that it reflects in–depth experience with Spring and J2EE as a whole. Rob is not only an author and open source developer—he is an application developer, like his readers. I firmly believe that the best writing on software development comes out of experience in the trenches, so this is my kind of book. If you're new to Spring, this book will help you understand its core concepts and the background in areas such as transaction management and O/R mapping that underpins them. If you're already using Spring, you will learn about features you haven't yet seen and hopefully, gain a deeper understanding of those features youre already using.” —Rod Johnson, Founder of the Spring Framework.